Die relevansie van die boek Prediker - Wyk, W. C. van (Hervormde teologiese studies, 1989)
The relevance of the book of Ecclesiastes Since the book of Ecclesiastes is generally neglected in biblical theology, systematic theology and the preaching of the church, the question is asked whether it is still relevant for the church. After a cursory look at some prominent ideas in the book, the relation between Ecclesiastes and the rest of the Bible is investigated, and a number of comparisons between Ecclesiastes and modern thinkers are considered. Finally an attempt is made at evaluating the relevance of the book of Ecclesiastes and indicating ways in which it might be explored for the theology and preaching of the church.